Rules of the house : family law and domestic disputes in colonial Korea - Lim, Sungyun, 1977- (Online access: De Gruyter De Gruyter Open Books., 2018)
"Rules of the House offers a dynamic revisionist account of the Japanese colonial rule of Korea (1910-1945) through the lens of women in the civil courts. Challenging the dominant understanding that women were victimized by the Japanese family laws (i.e., the Meiji Civil Code) and its patriarchal biases, Sungyun Lim argues that Korean women were not passive victims, but instead proactively struggled to expand their rights by aggressively participating in the Japanese colonial legal system. In turn, the Japanese doctrine of promoting progressive legal rights would prove advantageous to them. Following women and their civil disputes from the pre-colonial Choson dynasty, through the colonial times, and into the postcolonial reforms, this book presents a new and groundbreaking story about Korean women's legal struggles, revealing their surprising collaborative relationship with the colonial state. Lim thus expands the understanding of the Japanese assimilation policy in Korea, substantially revising the conventional focus on the Japanese assault on Korean ethnic identity. In so doing, she bridges the long-held fissure between historiography of the former metropole of Japan from the former colonies, and places colonial family laws in the larger context of legal reconfiguration of the Japanese empire"--Provided by publisher